2022
DOI: 10.1002/int.22858
|View full text |Cite
|
Sign up to set email alerts
|

A framework for evaluating sustainable renewable energy sources under uncertain conditions: A case study

Abstract: The need for energy sources in India has increased abnormally in recent years due to industrial and societal growth. To meet this demand, it was a necessary choice of renewable energy sources (RESs) as a solution to lack of nonrenewable energy sources. Due to the multiplicity of involved factors, selecting the most appropriate RESs is a multiattribute decision making (MADM) problem. There is a large number of work associated with the development of MADM techniques, especially under ambiguous and uncertain cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…To address the problem of end-of-life electronics recycling partner selection in an SVN environment, Rani and Mishra [26] created a novel similarity measure and introduced it into the combined compromise solution (COCOSO) to jointly identify the best partner. To assist India in selecting the finest renewable energy sources, Azzam et al [27] presented a new decision evaluation framework based on SVN information, and the study showed that the most suitable was wind energy. Rani et al [28] integrated SVN CRITIC and MULTIMOOR for food waste treatment technology selection.…”
Section: Svnssmentioning
confidence: 99%
“…To address the problem of end-of-life electronics recycling partner selection in an SVN environment, Rani and Mishra [26] created a novel similarity measure and introduced it into the combined compromise solution (COCOSO) to jointly identify the best partner. To assist India in selecting the finest renewable energy sources, Azzam et al [27] presented a new decision evaluation framework based on SVN information, and the study showed that the most suitable was wind energy. Rani et al [28] integrated SVN CRITIC and MULTIMOOR for food waste treatment technology selection.…”
Section: Svnssmentioning
confidence: 99%